IMPACT OF FDI, STAFF AND EXPENDITURE ON THE PROFITS OF INDIAN PRIVATE SECTOR BANKS - Chaudhry, Sahila; Kumar, Rakesh (International Journal of Psychosocial Rehabilitation, 2020)
is examined. The secondary data were collected from RBI publications, IBA Bulletins, Journals and other online databases from 2011-12 to 2017-18. The collected data were analyzed through descriptive and inferential statistical techniques like correlation, t-test and ANOVA with the help of PASW (18.0 Version). A significant relationship is found between FDI, Staff and Expenditure (independent variables), and profits per employee and profits per Branch (dependent variables). FDI, staff and expenditure (independent variables) explained the profits per employee (dependent variable) to the level of 44.5 percent only. On the other hand, profits per branch (dependent variable) are explained by the FDI, staff and expenditure (independent variables) to the level of 62.5 percent. There is no significant impact of FDI, staff and expenditure (independent variables) on profits per employee (dependent variable), whereas the impact of FDI, staff and expenditure (independent variable) on profits per branch (dependent variable) is found significant. Therefore, it is recommended that the banks should design suitable policies to reduce the level of NPAs and improve net interest margin. Further, regulators should liberalize the policies to catch the attention of investment from abroad for strengthening the infrastructure at branch level and extending the Indian banking throughout the world.